Comparison of the chronic and multigenerational toxicity of racemic glufosinate and l-glufosinate to Caenorhabditis elegans at environmental concentrations. (March 2023) - Zhao, Xu; Fu, Kan; Xiang, Kai-ping; Wang, Lan-ying; Zhang, Yun-fei; Luo, Yan-ping
Abstract: Glufosinate-ammonium, the second largest transgene crop resistant herbicide, is classified as a mobile persistent pollutant by the U.S. Environmental Protection Agencybecause of its slow decomposition and easy mobile transfer in a water environment. The chronic and multigeneration toxicity of this compound to environmental organisms are alarming. In this study, racemic glufosinate-ammonium and the effective isomer, l - glufosinate-ammonium, were used as the test agents. The developmental, neurotoxic and reproductive toxicities of Caenorhabditis elegans to their parents and progeny were studied by continuous exposure in water at concentrations of 0.1, 1, 10 and 100 μg/L. The causes of toxicity differences were analysed from oxidative stress and transcription levels. Through oxidative stress of C. elegans, racemic glufosinate-ammonium and l - glufosinate-ammonium both mediated the developmental toxicity (shortened developmental cycle, reduced body length and width, promoted ageingand decreased longevity), neurotoxicity (inhibited head swinging, body bending frequency and acetylcholinesterase [AchE] activity) and reproductive toxicity (significant reductions in the number of eggs and offspring in vivo and induced apoptosis of gonadal cells). These phenomena caused oxidative damage (protein and membrane lipid peroxidation) and further induced apoptosis. The changes in various indicators caused by racemic glufosinate-ammonium exposure were more significant than those caused by l - glufosinate-ammonium exposure, and the reproduction-related indicators were more significant than the developmental and neurological indicators. A continuous accumulation of toxicity was observed after multiple generations of continuous exposure. These research results provide a data reference for the ecotoxicological evaluation and risk assessment of glufosinate-ammonium and contribute to the revision and improvement of the related environmental policies of glufosinate-ammonium. Graphical abstract: Image 1 Highlights: Racemic glufosinate-ammonium was more cumulative toxic to C. elegans than l -glufosinate-ammonium. Glufosinate-ammonium affects glutathione circulation, which prevents eliminating ROS and mediates various toxicity.